Artificial Intelligence based Risk Management Framework for Distributed Agile Software Development - Khanna, Esha; Popli, Rashmi; Chauhan, Naresh (International Conference on Signal Processing and Integrated Networks (Online), 2021)
Distributed Agile Software Development blends the principles of agile to geographically separated teams and thereby combines the quality benefits of Agile Software Development with cost benefits of Distributed Software Development. Distributed Agile Software Development brings along new risks that arise due to the difference in working principles of Agile Software Development and Distributed Software Development. Identifying and managing these risks on time improves the quality of the software product and reduces the overall development cost. This work presents a novel Artificial Intelligence based framework for managing risks in Distributed Agile Software Development. The proposed framework will help the practitioners to timely identify and deal with associated risks and thereby reduce the cost and development time.